"What's Positive About Positive Rights?" Students' Everyday Understandings and the Challenges of Teaching Political Science. Issue 1 (2nd January 2018) - Ekström, Linda; Lundholm, Cecilia
ABSTRACT: A review of research into teaching and learning in political science education concludes that this literature emphasizes student outcomes and "show and tell" descriptions of pedagogical interventions (Craig2014 ). The present study instead aims to open the "black box" of conceptual learning in political science, illustrating the ambiguous role that everyday understandings of core concepts may play in the learning process. Starting from the conceptual change literature, we present findings on how everyday understandings influence learning regarding the concepts of "positive rights" and "anarchy, " resulting in various learning difficulties. The results suggest that teaching needs to explore and explain differences in meaning between scientific and everyday understandings.